Effects of the supplementation of distillers' grape residues on ruminal degradability, whole tract digestibility and nitrogen metabolism in sheep. Issue 5 (3rd September 2019) - Gao, Xinmei; Tang, Fu; Zhang, Fan; Jia, Chunyun; Yang, Zhenhua; Liu, Chenli; Gao, Wei
ABSTRACT: Five ruminally and duodenally cannulated Kazakh male lambs (30 ± 2.75 kg) maintained singly in a metabolic cage were used in a 5 × 5 Latin square experiment to investigate the effect of supplementing a ration with five different levels of distillers' grape residue (DGR) on ruminal degradability, whole tract digestibility and nitrogen (N) metabolism of growing lambs. The rations were isoenergetic and isonitrogenous and contained 0, 3.85, 7.70, 11.55 and 15.41% DGR (DM basis). Each experimental period lasted for 18 d: 10 d for adaptation to the dietary treatment and 8 d for faecal, urinary, ruminal and duodenal digesta sample collections. The outflow rate of ruminal digesta increased ( p = 0.032) linearly with the increased level of dietary neutral detergent fibre content, caused by the supplementation of DGR. As a result, the effective degradability of dry matter and crude protein decreased significantly with the treatments. Although the dietary intake of N, duodenal flow of total N, and the endogenous N at the duodenum were not affected by experimental treatments, N fractions in the digesta were altered. Ruminal microbial N decreased ( p < 0.01) linearly; in contrast, ruminal un-degradable protein increased linearly ( p < 0.01) in response to the increased addition of DGR. Although there was no significant difference in faecal N among treatments, N retention was increased linearly ( p = 0.014), owing to the remarkable reduction ( p = 0.016) of urinary N excretion with an increasing level of DGR. The results indicate that the DGR has some potential benefits of increasing the supply of bypass protein and of improving the utilisation efficiency of N for sheep. Therefore, the supplementation of DGR in ruminant feeding is recommended at levels not exceeding 10% of the diet.